REDEFINING FEMALE IDENTITY IN INTERACTIVE MEDIA: DECONSTRUCTING GENDER STEREOTYPES THROUGH THE CHARACTER YUNA IN GHOST OF TSUSHIMA - Aryana, Putri Sri; -, Rostineu (UI Scholars Hub, 2026)
This study examines the deconstruction of female gender stereotypes through the character Yuna in the game Ghost of Tsushima. The analysis employs a qualitative approach that explores narrative, visual, and gameplay aspects. The theoretical framework draws on Judith Butler’s gender performativity, Marie-Laure Ryan’s digital narrative theory, and Stuart Hall’s representation theory to identify forms of resistance to traditional gender norms reflected in the game industry. The findings indicate that Yuna emerges as an active agent who influences the protagonist’s ideological development, plays a significant role in shaping the overall narrative direction, and avoids visual objectification. This study is expected to contribute to gender studies in interactive media and highlight the potential of video games as a medium capable of presenting more inclusive and progressive representations of women in popular culture.